Risk factors of refracture and morbidity during removal of titanium pediatric proximal femoral locking plates in children with cerebral palsy - İnan, Muharrem; Sarıkaya, İlker Abdullah; Şeker, Ali; Güven, Mehmet Fatih (Lippincott Williams and Wilkins, 2016)
Background: Pediatric proximal femoral locking plates (PFLPs) are widely used when performing proximal femoral osteotomy in children with cerebral palsy (CP). The purpose of this study is to report the difficulties and risk factors of titanium PFLPs removal in CP. Methods: PFLP removal was performed in 58 hips of 33 patients (17 males, 16 females). The mean age at the time of surgery (plate removal) was 10.9 (range, 5.7 to 19.2) years. The patients were divided into 2 groups as group 1 and 2, if any difficulty was observed during surgery or not. Results: Difficulty was not detected in 42 (72.4%) hips (group 1). Difficulties were encountered in 16 (27.6%) hips (group 2). A total of 364 screws were used (259 in group 1, 105 in group 2). The mean plate screw density ratios were 0.88 in group 1 and 0.94 in group 2. The difference between group 1 and 2 was statistically significant. The mean duration between the insertion and removal of the PFLP was 14.9 months (11.9 mo in group 1, 22.7mo in group 2). The difference between group 1 and 2 was statistically significant. The screw heads were cut and the shafts were left in the bone in 4 hips (4 screws); 3 of these 4 screws were calcar screws. Therefore, calcar screw application can be accepted as a handicap for screw removal. Conclusions: As a conclusion, this study suggested that difficulty in titanium PFLP removal in CP is common and PFLP removal is not a harmless procedure. A longer time from internal fixation to removal, increased plate screw density ratio, and calcar screw application are risk factors for difficulties in titanium PFLP removal in CP.
Keywords: Cerebral Palsy; Complication; Pediatric Hip Plate; Plate Removal; Risk Factors